Different Parameters Affecting to Production of Curcumin-Dry-Salted Frog (Hoplobatrachus Rugulosus) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Frog (Hoplobatrachus rugulosus) meat is an attractive food choice in international market. Frogs are mainly collected from nature and with the rising human activities. Consumption of frog meat has increased in the last few years. Frog production has been growing up and down many times due to the spontaneous development of farmers. Meanwhile frog processing is not developed in Vietnam thus the export volume of this product is limited. Most of frogs are supplied directly to the market for consumers. It’s necessary having post-harvest management including the processing of this species into the value-added foodstuff. From that, commercial frog value chain can be enhanced. Most traditional sun dried frogs do not meet the expected standard for human consumption due to the infestation of the products by the fly, insect larvae, contaminants and spoilage. The simplicity of the salting process, the low cost of production and the easy combination with curcumin could be considered as a preservative. Objective of this research focused on the processing of frog into the curcumin-dry-salted product by salting and drying method. Different technical experiments were investigated such as the effect of salt, curcumin ratio during soaking, temperature of drying, and packaging storage to chemical, microbial and sensory characteristics of the finished product. Results revealed that dry salting was better than wet salting. With addition of 0.75% of curcumin, drying at 50oC in 3 hours, the curcumin-dry-salted frog products had the good physicochemical, microbiological and sensory characteristics. By preserving under vacuum at 4oC, the curcumin-dry-salted frog could be maintained shelf-life for 12 months without any deterioration.Keywords: Frog, Hoplobatrachus rugulosus, Curcumin, Salting, drying, Vacuum, Shelf-life.